The Troubles with Harry: Freedom, America, and God in John Updike's Rabbit Novels - Pasewark, Kyle A. (Religion and American culture, 1996)
[I] had all of Shillington to say, Shillington and Pennsylvania and the whole mass of middling, hidden, troubled America to say.… In the beauty of the lilies Christ was born across the sea—this odd and uplifting line from among the many odd lines of “The Battle Hymn of the Republic” seemed to me, as I set out, to summarize what I had to say about America, to offer itself as the title of a Continental magnum opus of which all my books, no matter how many, would be mere installments, mere Starts at the hymning of this great roughly rectangular country severed from Christ by the breadth of the sea. John Updike's corpus is punctuated forcefully by his own magnum opus, the Rabbit series, a tetralogy that is simultaneously literature, cultural critique, and theology.